Moldova Financial Sector Assessment Program : Oversight and Supervision of Financial Market Infrastructures and Risk Assessment of Central Securities Depositories - International Monetary Fund (Washington, DC, 2015)
The approach taken by authorities in the oversight and supervision of FMIs is important in promoting and maintaining financial stability in Moldova. While well-functioning FMIs can greatly improve the efficiency, transparency, and safety of financial systems, they can also concentrate systemic risk, which requires effective oversight and supervision to achieve public policy objectives. In the context of Moldova, the authorities are confronted with a national decision to create a single CSD that has good governance, robust risk management practices, and financial soundness. Vulnerabilities in FMIs could potentially undermine the implementation of monetary policy, or generate systemic disruptions in the financial markets, and more widely across the economy. A problem may be initiated by the inability of a participant to settle its obligations, or by operational failures of the system as a whole. The resulting default may be passed on to other participants, and get transmitted across financial systems and markets, threatening their stability. This note reviews the oversight and supervisory framework for FMIs in Moldova. In this note, FMIs cover payment systems, central securities depositories, and securities settlement systems. Payment systems were assessed in the 2008 Republic of Moldova FSAP Update and are not covered in this note. Securities registrars, which play a key role in the capital markets, are not FMIs and are assessed under principle 11 on CSDs of the PFMIs. The analysis was based on the authorities’ answers to the IMF’s questionnaire, IMF and World Bank technical assistance reports, and background documentation. The mission met with representatives from the NBM, NCFM, MSE, NSD, and independent registrars. This note was prepared based on the information available in February 2014. The note includes (i) an overview of the FMIs and description of past and ongoing reforms, and (ii) an assessment of the main issues at stake.